Effect of Two Formulations of Sufentrazone on Weed Control in Tobacco (Nicotiana Tabacum L) - Mashayamombe , Bertha K.; Mazarura , Upenyu; Chiteka , Albert (Asian Journal of Agriculture and Rural Development, 2013)
Field studies were done to compare the weed control efficacy of a wettable granular formulation (Authority 75 WG) and a suspension concentrate formulation (Authority 48 SC) of the herbicide sulfentrazone. A 6 x 2 factorial experiment was laid out in a split plot design to evaluate the effect of the two herbicides on the weed control efficacy in tobacco. The first factor was herbicide which had 6 levels and the second factor was weeding which had 2 levels. One rate of the wettable granular formulation at 0.225 kg/ha, four different rates of the suspension concentrate formulation at 0.165, 185, 0.205 and 0.225 kg a.i. /ha and the untreated control were tested. These were split into two weeding levels (weedy and weed free). The weed free plots were weeded every other week for 12 weeks beginning two weeks after transplanting tobacco. The treatments were combined to give 6 treatments for each main plot. These were replicated four times. This work reported efficacy data from the weedy plots. Weed counts were measured at 4 and 8 weeks after transplanting (WAP) and weed dry-mass at 8WAP. Results show that both formulations at all tested rates poorly controlled broadleaf and grass weeds while nutsedge control was excellent. This study showed that the rates used were too low to effectively control grasses and broadleaved weeds while they were adequate for control of nutsedge. We therefore suggest that this material fills an important niche as a nutsedge material with post emergent nutsedge control. Further work should look at herbicide mixtures in order to improve grass and broadleaf control.